Improved ephemerides of natural satellites. (Research'eu results magazine)
Measuring the position of natural satellites is essential to ensuring a spacecraft has enough propulsion to reach its target. EU-funded scientists have calculated premise ephemerides for planetary moons by taking physics into account.